PEMBUATAN ILUSTRASI BUKU POP-UP SEBAGAI MEDIA PENGENALAN HURUF DAN NAMA-NAMA BINATANG PADA ANAK USIA DINI - EDHO, BAKHTAWAR (Universitas Negeri Semarang, 2015)
This study project creation through four processes, namely: 1 ) setting goals, 2 ) data collection, 3 ) pre-production process, and 4 ) the production process . Preproduction phase include making a sketch , vectorization, and printing and production processes that include cutting , scrapping out , hand assembly, and finishing. In the making of this work resulted in two works illustrated books , namely ; 1) The pop -up book illustration of a combination consisting of 26 illustrations and pop -up animals that are sorted in alphabetical order and 2 ) ilutrasi pop-up book volvelle or wheel divided into four series, namely ; a) water animals series , b ) winged animals series, c ) urban animals series , and d ) wild animals series. With the study project is expected that art students especially design students can design a good design work , innovative and communicative so that they can make a positive contribution through works of art and design .